A new Markalius species from the Cretaceous/Paleogene boundary of the Neuquén Basin (Argentina) - Do Monte Guerra, Rodrigo; Concheyro, Graciela (Journal of Nannoplankton Research)
Study of a Cretaceous/Paleogene (K/Pg) boundary section in the Jagüel Formation, Neuquén Basin,Argentina, has revealed a new calcareous nannofossil species, Markalius neuquenesis sp. nov. This new species is medium to large in size (7.3 to 8.03 μm), with a broad, birefringent tube cycle divided into four sectors, each with at least one small perforation. The species is rare to few in abundance in the upper Maastrichtian through lower Danian Jagüel Formation and has also been observed in the Danian of the North Atlantic Ocean Fil: Do Monte Guerra, Rodrigo. Universidad de Vale do Rio dos Sinos; Brasil Fil: Concheyro, Graciela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina